New and known Halichoanolaimus de Man, 1886 species (Nematoda: Selachinematidae) from New Zealand’s continental margin - Leduc, Daniel (European Journal of Taxonomy, 2020)
The Selachinematidae is a globally distributed family of predatory nematodes found from shallow waters to the abyssal plain. Here, three new species of Halichoanolaimus de Man, 1886 (H. ossilagulus sp. nov., H. funestus sp. nov. and H. pumilus sp. nov.) and one known species (H. ovalis Ditlevsen, 1921) are described from the New Zealand continental margin, thus bringing the total number of selachinematid species recorded from the New Zealand region to 14 and the total number of species of Halichoanolaimus to 26. The range of H. ovalis is extended from the Southern Ocean to the Southwest Pacific Ocean (latitude 42° S to 53° S); the depth range of this species, which was originally described from the littoral zone, is also extended to 1061 m depth. Dorsosublateral rows of pore complexes and pseudocoelomocytes, features that have either rarely or not been recorded previously in the genus, were observed in all four species described here. The taxonomic significance of these features remains to be ascertained for the family and will require observations of other species of Halichoanolaimus and selachinematid genera. Pseudocoelomocytes and pore complexes may have an excretory function, thus aiding to process the waste products of digestion in selachinematid taxa with a blind intestine.